2010
DOI: 10.2164/jandrol.110.011197
|View full text |Cite
|
Sign up to set email alerts
|

GLUTs and Mammalian Sperm Metabolism

Abstract: Mammalian cells use glucides as a substrate that can be catabolized through glycolitic pathways or oxidative phosphorylation, used as a source of reducing potential, or used for anabolic aims. An important role in supplying cells with energy is played by different membrane proteins that can actively (sodium-dependent glucose transporters) or passively (glucose transporters; GLUT) transport hexoses through the lipidic bilayer. In particular, GLUTs are a family of 13 proteins that facilitate the transport of sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 66 publications
2
75
0
7
Order By: Relevance
“…Although proteins of the SGLT family have been reported to be present in mammalian sperm [19], at this moment, there is a general consensus in considering that GLUT proteins are the most important hexose uptake mechanism of mammalian sperm [20].…”
Section: Overview Of Mammalian Sperm Energy Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although proteins of the SGLT family have been reported to be present in mammalian sperm [19], at this moment, there is a general consensus in considering that GLUT proteins are the most important hexose uptake mechanism of mammalian sperm [20].…”
Section: Overview Of Mammalian Sperm Energy Metabolismmentioning
confidence: 99%
“…These proteins differentiate themselves by subtle structural changes that, in turn, lead to great differences in the affinity for separate sugars and tissue specificity [17,18]. Regarding mammalian spermatozoa, the GLUTs that have been detected until now comprise GLUT-1, GLUT-2, GLUT-3, GLUT-5, GLUT-8, and GLUT-9, whereas the presence of the insulin-dependent GLUT-4 seems doubtful [20]. An intriguing question regarding GLUTs is why a cell, such as the mature mammalian spermatozoon, requires the presence of at least six separate GLUT hexose transporters to uptake a very common external energy sources such as monosaccharides.…”
Section: Overview Of Mammalian Sperm Energy Metabolismmentioning
confidence: 99%
“…DIET AND EXERCISE IMPROVE SPERM FUNCTION IN OBESE MICE energy source (15). It has been found that glucose, not fructose, is needed for fertilization and is specifically required during sperm oocyte binding and embryo viability in the mouse (72).…”
Section: E776mentioning
confidence: 99%
“…In fact, mammalian sperm require metabolic energy for a variety of functions (Williams & Ford 2001, Ferramosca & Zara 2014, and it is known that human spermatozoa obtain a significant proportion of their energy from glycolysis (Williams & Ford 2001). Nevertheless, the origin of ATP for sperm motility is still being intensely discussed (Ford & Harrison 1981, Williams & Ford 2001, Ruiz-Pesini et al 2007, Bucci et al 2011, Piomboni et al 2012.…”
Section: Effects Of Substrate Availability On Spermatozoa Functionalitymentioning
confidence: 99%